2004
DOI: 10.1128/aem.70.8.4980-4988.2004
|View full text |Cite
|
Sign up to set email alerts
|

Model System for Growing and Quantifying Streptococcus pneumoniae Biofilms In Situ and in Real Time

Abstract: Streptococcus pneumoniae forms biofilms, but little is known about its extracellular polymeric substances (EPS) or the kinetics of biofilm formation. A system was developed to enable the simultaneous measurement of cells and the EPS of biofilm-associated S. pneumoniae in situ over time. A biofilm reactor containing germanium coupons was interfaced to an attenuated total reflectance (ATR) germanium cell of a Fourier transform infrared (FTIR) laser spectrometer. Biofilm-associated cells were recovered from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 22 publications
(21 reference statements)
3
91
0
3
Order By: Relevance
“…The importance of biofilm production in the pathogenesis of respiratory tract infection caused by other common respiratory pathogens such as H. influenzae (21, 44) and S. pneumoniae has been well described (45). Less clear is whether these biofilms require the participation of neuraminidases for biosynthesis or modification.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of biofilm production in the pathogenesis of respiratory tract infection caused by other common respiratory pathogens such as H. influenzae (21, 44) and S. pneumoniae has been well described (45). Less clear is whether these biofilms require the participation of neuraminidases for biosynthesis or modification.…”
Section: Discussionmentioning
confidence: 99%
“…Budhani and Strutters (13) used a continuousculture system (sorbarod filter) to determine antimicrobial susceptibilities of S. pneumoniae biofilms, while Waite et al (70) employed the same continuous-culture biofilm system to investigate variation in capsule production upon biofilm formation by serotype 3 pneumococci. Likewise, Donlan et al (23) used a continuous-culture model system allowing the simultaneous measurement of cells and exopolysaccharide of biofilm-associated S. pneumoniae in situ over time.…”
mentioning
confidence: 99%
“…Moreover, the ability to form biofilms has been proposed to play an important role in otitis media with effusion and recurrent otitis media, which commonly involve Haemophilus influenzae and S. pneumoniae (26, 28). Recently, it was demonstrated that S. pneumoniae can form biofilms in vitro (4,26,82) and that this mode of living is accompanied by the differential expression of about 30% of the S. pneumoniae proteome and the de novo synthesis of about 200 proteins (4). Moreover, Oggioni and colleagues (65) reported that the transcriptional profile of several known virulence-related genes in S. pneumoniae isolated from lungs…”
mentioning
confidence: 99%